Efficient multinucleotide deletions using deaminase-Cas9 fusions in human cells. (October 2022) - Chen, Siyu; Liu, Zhiquan; Yu, Hao; Lai, Liangxue; Li, Zhanjun
Abstract: CRISPR/Cas9 system is a robust genome editing platform in biotechnology and medicine. However, it generally produces small insertions/deletions (indels, typically 1–3 bp) but rarely induces larger deletions in specific target sites. Here, we report a cytidine deaminase-Cas9 fusion-induced deletion system (C-DEL) and an adenine deaminase-Cas9 fusion-induced deletion system (A-DEL) by combining Cas9 with rat APOBEC1 (rA1) and TadA 8e, respectively. Both C-DEL and A-DEL improve the efficiency of deletions compared with the conventional Cas9 system in human cells. In addition, the C-DEL system generates a considerable fraction of predictable multinucleotide deletions from 5′-deaminated C bases to the Cas9-cleavage site and increases the proportion of larger deletions at the target loci. Taken together, the C-DEL and A-DEL systems provide a practical strategy for producing efficient multinucleotide deletions, expanding the CRISPR/Cas9 toolsets for gene modifications in human cells.